TAXATION AND ECONOMIC SUSTAINABILITY - Kalendienė, Jonė; Pukelienė, Violeta (Ekonomika, 2011)
Macroeconomic theory says that taxes play a repressing role in an economy. Introduction of new forms of taxation, the increase of tax rates and augmentation of tax income of the Government puts a downturn risk on consumption and therefore on economic growth. Knowing that, governments of different countries start to competing among themselves by lowering corporate tax rates and trying to boost economic growth by using foreign investments. On the other hand governments are pushed to lower personal tax rates in order to satisfy their electorate. It has been strongly believed that countries with lower tax rates have better prospects for the future growth. However, small tax income is limiting governmental spending and might cause serious imbalances in the economy. As the Irish example shows, smaller taxes cannot guarantee a sustainable growth of the economy. Thus, the relationship between taxation and economic development needs rethinking.This study aimed to test the efficiency of taxation in terms of sustainable economic development and to discuss the factors that are the most important here.A comparative analysis of EU countries was used in the research. The results suggest that the harmfully small tax rates could have violated the sustainability of some European economies.